Pengembangan Aplikasi Monitoring Penyakit Hipertensi dan Diabetes Mellitus Terintegrasi - Siti Minasari; Mahalul Azam; Sri Ratna Rahayu (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
Non-communicable diseases (NCDs) are a health development priority at this time. The increase in the prevalence of PTM over the last few years. Hypertension and diabetes mellitus are PTM that have increased cases. Changes in behavior and lifestyle are risk factors for hypertension and diabetes mellitus. The recording and reporting of officers related to PTM still experience difficulties in routine monitoring of treatment and patient visits. There is currently no integrated information system between Hypertension and Diabetes Mellitus to monitor patient compliance for treatment. The purpose of the study was to develop an integrated application system for monitoring hypertension and diabetes mellitus in the city of Semarang. The type of research conducted is rapid and development (RAD), with a qualitative approach. The research stage: is the identification of information system development needs, is database design and application interface, and implementation of android application model development on a small scale (three prolanis officers). The subjects of this study were three prolanis officers and five patients with primary hypertension and diabetes mellitus aged 46 to 55 years. Results: system development by analyzing user data needs of officers and patients include patient identity, patient examination results, follow-up on examination results, patient referrals, education on healthy menus and ways to prevent hypertension and diabetes mellitus, the reminders to take medication, and results of routine examinations. Database design and application interface described through DFD and ERD. Implementation and function tests carried out on fully developed applications.